Altitude-Driven Differences in Thermal Units, Growth and Quality of Beetroot (Beta vulgaris L.) - Fajriani, Sisca; Alifah, Yasmina Nur; Ariffin, Ariffin; Setiawan, Adi (CV. Komunitas Dunia Peternakan, 2025)
Beetroot is traditionally cultivated in highland areas; however, limited land availability and growing market demand have encouraged its expansion into mid-altitude regions. Thermal unit accumulation is an important factor in predicting crop phenology and harvest time. This study aimed to analyze the thermal unit requirements, growth performance, and tuber quality of beetroot cultivated at different altitudes in East Java, Indonesia. The experiment was conducted from August to December 2024 in greenhouses located in Jatimulyo, Malang (445 m a.s.l., midland) and Sumberejo, Batu (873 m a.s.l., highland) using 250 plants of the Boro variety with a single-plant observation method. Results showed that midland-grown plants reached harvest earlier (84 DAS; 1,527.3 °C·day) compared to highland-grown plants (104 DAS; 1,572.7 °C·day). Higher thermal accumulation had a strong positive correlation with soluble solids (r = 0.74) and a strong negative correlation with fresh tuber weight (r = –0.79), indicating that increased heat enhanced sugar synthesis but reduced biomass. Highland conditions produced larger tubers, while midland conditions improved betacyanin and sweetness levels, showed that altitude-driven temperature differences affect both yield and quality, suggesting that highland cultivation is suitable for fresh markets, whereas midland cultivation is more appropriate for industrial uses such as natural food colorants and processing industries.